Tele-remote controlling and monitoring ... [et al.] / [mikrofilem] - 286090 Lim, Albert Wee Tap (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1999